IMPROVING THE QUALITY OF EDUCATION STUDENTS AT THE DEPARTMENT OF THERAPEUTIC DENTISTRY BY INTRODUCTION INTO THE TRADITIONAL SYSTEM OF EDUCATION COLLECTIVE INNOVATIVE STUDIES - Petrushanko, T.A.; Gasyuk, N.V.; Nikolishyna, E.V.; Popovich, I.J.; Іваницький, І.О. (World of Medicine and Biology, 2013)
In the article the results of the Students' Scientific society of therapeutic Stomatology HSEI Ukraine "Ukrainian Medical Stomatological Academy" on the implementation of the traditional system of collective innovative training sessions. Using their experience, we can recommend this teaching strategy in higher education, which enables communication style of communication, raising curiosity and deep knowledge of the cycle of pathology of the oral mucosa and periodontal tissues.
Keywords: consciousness; innovation; thinking and education